1999
DOI: 10.1161/01.hyp.33.6.1392
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Abnormalities in Arterial Compliance Identified by Pressure Pulse Contour Analysis

Abstract: Abstract-The objective of this study was to evaluate age-related changes in pulsatile arterial function. Aging alters arterial pulsatile function and produces consistent changes in the pressure pulse contour. A reduced systemic arterial compliance that can be derived from analysis of the pulse contour is regarded as the best clinical index of impaired pulsatile arterial function and may mark the presence of early vascular damage. We analyzed intra-arterial brachial artery waveforms in 115 healthy normotensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
208
1
13

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(234 citation statements)
references
References 49 publications
12
208
1
13
Order By: Relevance
“…28 Ageing produces a progressive decline in both large artery and small artery elasticity consistent with the well-recognized relationship between age and the risk for cardiovascular events. 29 In contrast, CRP did not increase with age and did not correlate with small artery elasticity, a marker for endothelial dysfunction, or with the biochemical markers for atherosclerosis risk. Thus CRP appears to serve as an accelerator of atherosclerosis in individuals who exhibit early disease, not as an initiator of the process (Table 5).…”
Section: Discussionmentioning
confidence: 84%
“…28 Ageing produces a progressive decline in both large artery and small artery elasticity consistent with the well-recognized relationship between age and the risk for cardiovascular events. 29 In contrast, CRP did not increase with age and did not correlate with small artery elasticity, a marker for endothelial dysfunction, or with the biochemical markers for atherosclerosis risk. Thus CRP appears to serve as an accelerator of atherosclerosis in individuals who exhibit early disease, not as an initiator of the process (Table 5).…”
Section: Discussionmentioning
confidence: 84%
“…4 A wrist stabilizer was positioned on the right wrist using two hook and loop straps in order to gently immobilize the wrist and stabilize the radial artery, making it readily accessible for placement of the Arterial pulsewavet Sensor. The Sensor electronically adjusts itself automatically in order to obtain an acceptable waveform.…”
Section: -10mentioning
confidence: 99%
“…Reduced arterial elasticity is a hallmark of ageing that precedes apparently obstructive atherosclerosis and cardiovascular events. [1][2][3][4] Our recent studies demonstrated that decreased arterial elasticity is associated with endothelial dysfunction in humans with ageing and measurement of arterial elasticity may be used as a novel index for the determination of endothelial function. 5 The mechanisms responsible for the age-related reduction in arterial elasticity and endothelium-dependent vasodilatation, however, have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A computer-based third-order, 4-element modified Windkessel model of the circulation is used to match the diastolic pressure decay of the tonometrically obtained waveforms and to quantify changes in arterial waveform morphology in terms of SVR, C1, C2, and L. The values of C1, C2, and L given in the report are weighted averages of the values obtained on individual waveforms during a 30-second recording period. 26,27,39 SVR is calculated as mean arterial pressure (MAP) divided by cardiac output (CO). MAP is derived from the waveform analysis (after calibration with the oscillometrically obtained blood pressure) by integrating the area under each beat and then calculating the average of all beats included in the analysis.…”
Section: Hdi/pulsewave Research Cardiovascular Profiling Instrumentmentioning
confidence: 99%